Biodegradable epoxy resin from vanillin with excellent flame-retardant and outstanding mechanical properties. (July 2022) - Ma, Jinpeng; Li, Guanxi; Hua, Xueni; Liu, Ning; Liu, Zhe; Zhang, Fan; Yu, Liangliang; Chen, Xue; Shang, Lei; Ao, Yuhui
Highlights: A bio-based aromatic thermoset epoxy resin(MVE) was synthesized from Schiff base compound. Schiff base and melamine structure promote carbonization and reduce fire hazard of thermoset epoxy resin. The new epoxy thermoset exhibits superior mechanical properties and advantageous degradability. This paper provides a new strategy for simultaneously enhancing the mechanical properties and fire-safety performance. Abstract: In this work, the sustainable and biodegradable flame retardant epoxy resin was designed and prepared to replace resource-limited petrochemicals, especially, bisphenol A type epoxy resin (DGEBA). A renewable chemical, vanillin was condensation to produce Schiff-based compound (MAV) employing the novel epoxy resin (MVE) through the epoxidation reaction. The epoxy equivalent of MVE was approximately 217 g/eq and used non-isothermal differential scanning calorimetry (DSC) to study the curing kinetics of MVE/DDM (4, 4′-Diaminodiphenylmethane). After curing by DDM, they exhibit outstanding mechanical property and a residual char rate as high as 41.77%, excellent inherent flame retardancy and limited oxygen index (LOI) value higher than 34%, far superior to DGEBA. The total heat release (THR) and smoke release rate (SPR) of MVE/DDM decreased by 67.44% and 64.69% compared with DGEBA/DDM, respectively. The mechanisms for the enhancement of flame retardancy by intrinsic flame retardant epoxy resin were investigated. Moreover, the sustainable epoxy crosslinking could degrade completely benefited from the structure of the Schiff base in the moderate conditions (THF: H2 O = 6: 4, 50 °C) within few hours. Overall, this work contributes a multifunctional vanillin-based epoxy monomer and environmentally friendly thermosets with high mechanical property and enhanced flame retardancy. Graphical abstract: Main performance roadmap of degradable epoxy resin. Image, graphical abstract